An Efficient Ugi‐Azide Four‐Component Approach for the Preparation of Novel 1‐(1H‐tetrazol‐5‐yl)‐10‐chloro‐1, 2, 3, 4‐tetrahydropyrazino[1, 2‐a] Indoles. (4th March 2019) - Salahi, Saleh; Ghandi, Mehdi; Abbasi, Alireza
Abstract : The synthesis of novel 1‐(1 H ‐tetrazol‐5‐yl)‐10‐chloro‐1, 2, 3, 4‐tetrahydropyrazino[1, 2‐ a ] indole derivatives starting from the initially prepared 1‐(2‐bromoethyl)‐3‐chloro‐1 H ‐indole‐2‐carbaldehyde is described. A variety of likely biologically relevant pyrazino[1, 2‐ a ] indole‐based 1, 5‐disubstituted tetrazoles was obtained in moderate to high yields via an Ugi‐azide reaction. These reactions presumably proceed by the imine formation, intramolecular cyclization to iminium ion, and nucleophilic addition tandem reactions, respectively. Abstract :